THE ROLE OF GENDER IN ASSESSMENTS OF EMPLOYEES' PSYCHOSOCIAL RISKS TO WORK - Karabiber, Hulusi; Kurt, Sena; Gurol, Yonca Deniz (EMERALD GROUP PUBLISHING LTD, 2023)
Psychosocial risks in the workplace include occupational risks such as stress, harassment, burnout, and workplace violence that affect the physical integrity and mental health of employees (Bunker et al., 2003). Work-related psychosocial risks are relevant to the design and management of the job and its social and organizational contexts (Leka, Griffiths, & Cox, 2003). In this study, it was investigated which factors are effective in the psychosocial risk assessments of blue-collar workers in Turkey and whether there is a significant effect of gender in these assessments. The sample of the research consists of 663 employees working in a production facility in Tekirdag. The results showed that cognitive demands, the meaning of work, and development opportunity variables differed by gender from psychosocial risks. Women evaluate lower scores than men in expressions related to cognitive demands, the meaning of work, and development opportunities. Quantitative demands, emotional demands, burnout, and job satisfaction did not differ significantly by gender. The findings provide an understanding of the potential risks in the working conditions of blue workers in Turkey and provide the basis for future research.
Keywords: Blue collar; psychosocial risks; gender; job demand and sources; job demands; cognitive demands; BLUE-COLLAR WORK; BURNOUT; QUESTIONNAIRE; ENGAGEMENT; POSITION; WOMEN; LIFE; Business & Economics; Social Sciences - Other Topics